Solitary / #2. - Smith, Alexander Gordon, 1979- (Escape from Furnace, 2010)
Alex Sawyer and his friends end up in even more trouble after being caught trying to escape from Furnace Penitentiary for young offenders, and they find themselves struggling to survive solitary confinement.